(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article presents the experimental results on the influence of the installation angles of the support disc relative to the vertical on the performance indicators of a plow. It was determined that when the installation angle of the support disc relative to the vertical is 0°, the supporting surface is insufficient. As a result, during inversion plowing, the actual working width of the plow exceeds the design working width by 5.1 cm and 8.2 cm, respectively. At this angle, the plow operates with lateral deviation. When the installation angle of the support disc relative to the vertical is in the range of 10° to 20°, the plow operates without lateral deviation, and therefore its actual working width does not significantly exceed the design working width. However, when the installation angle increases from 20° to 30°, the support disc does not sufficiently rest on the bottom of the furrow, which leads to an increase in the plow’s working width.